Lateral and functional asymmetries in the lower limbs of college-level female handball players - Renan Vieira Barreto; Claudio Oliveira Assumpção; Natália de Menezes Bassan; Adalgiso Coscrato Cardozo; Camila Coelho Greco; Benedito Sérgio Denadai; Ronei Silveira Pinto; Leonardo Coelho Rabello Lima (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aim: The present study aimed to screen for differences in isokinetic peak torque, hamstrings-to-quadriceps ratio, and proprioception within the lower limbs of female handball athletes. Methods: Twelve college-level female handball athletes with no previous experience with resistance training performed five maximal isokinetic contractions of the knee extensors and knee flexors to determine isokinetic peak torque and hamstring-to-quadriceps ratios. Proprioception was determined by assessing passive position sense on an isokinetic dynamometer. Results: The athletes presented significantly greater (p < 0.01) knee extensors isometric peak torque for the jumping limb (144.9 ± 23.1) when compared to the non-jumping limb (132.9 ± 21.5). The Hamstrings-to-quadriceps ratio was below 0.6 for both limbs, being significantly greater (p < 0.01) for the non-jumping limb (0.56 ± 0.08) when compared to the jumping limb (0.50 ± 0.08). Conclusion: Female handball athletes that do not engage in resistance training can experience functional bilateral asymmetries in the knee extensors and knee-joint instability, as assessed by the hamstrings-to-quadriceps ratio due to the asymmetric characteristics of handball. Regular strength training might correct such asymmetries and instabilities.